Are Farmers Made Whole by Trade Aid?. Issue 2 (3rd May 2020) - Janzen, Joseph P.; Hendricks, Nathan P.
Abstract: The USDA provided roughly $23.5 billion in Market Facilitation Program payments to compensate farmers for market losses due to retaliatory tariffs imposed by China and other countries. We examine the distribution of these payments across crops, farms, and regions. Payment rates are larger than estimated price impacts of retaliatory tariffs for most commodities—the difference is especially large for cotton and sorghum. Payment rates relative to farmland cash rent or on a per‐farm basis are greatest in the South. While payments exceed the tariff‐related price impact in the short run, the program may not compensate for long‐run losses due to the trade conflict.